PERAN KEPALA SEKOLAH UNTUK MENINGKATKAN PROFESIONALISME GURU DI SMA NEGERI 2 TOMA TAHUN PELAJARAN 2020/2021 - Efaluas Finowa’a; Fowa’a Duha (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aims to determine the role of school principals in improving teacher professionalism at SMA Negeri 2 Toma, Toma District, South Nias Regency. The research method used is qualitative by using data collection techniques in the form of observation, interviews and documentation with an emphasis on informant data sources: school principals, vice principals, administrative staff and teachers to confirm the validity of the data obtained. From the results of this study revealed two findings, namely: (1) to determine the role of school principals in improving teacher professionalism at SMA Negeri 2 Toma, Toma District, South Nias Regency, (2) to find out the steps of principals in improving teacher professionalism in SMA Negeri 2 Toma, Toma District, South Nias Regency. From the explanation above, it can be concluded that the principal's efforts in improving teacher professionalism, (1) the principal conducts training (Diklat), Subject Teacher Consultation (MGMP) and (2) involves teachers in an effort to encourage and encourage teachers to participated in various trainings and seminars in improving teacher professionalism at SMA Negeri 2 Toma, Toma District, South Nias Regency.